A Rare Case of Acute Liver Failure Secondary to Diffuse Hepatic Infiltration of Small Cell Neuroendocrine Carcinoma - Yan, Ping; Liu, Yu; Wang, Qing; Chen, Xia (Frontiers in Oncology, 2021)
Background Malignant liver infiltration is an uncommon cause of acute liver failure (ALF) and has rarely been reported. Case Presentation We present a patient with progressive jaundice and dissociation of bilirubin and aminotransferases, who had no history of relevant liver diseases or tumor except the use of Chinese traditional drugs for a cold. An abdominal computed tomography (CT) scan showed ascites without hepatic focal lesions. Laboratory studies revealed no evidence of hepatitis or underlying autoimmune disorders. Following 8 days of conservative management ALF rapidly worsened. Contrast-enhanced CT revealed diffuse regenerative nodules in the liver. The patient underwent liver biopsy, which demonstrated that the liver was infiltrated by pulmonary neuroendocrine tumor classified as small cell lung cancer. The patient died 13 days after diagnosis. Discussion and Conclusions This case represents a rare cause of ALF induced by pulmonary neuroendocrine tumor of small cell type and illustrates the importance of prompt biopsy in an unknown cause of ALF.